Advances in Time Series Data Methods in Applied Economic Research International Conference on Applied Economics (ICOAE) 2018 - Tsounis, Nicholas; Vlachvei, Aspasia (Springer Proceedings in Business and Economics, 2018)
XV, 560 p. 76 illus., 61 illus. in color.